Peran Budaya Organisasi dalam Pembentukan Employee Engagement Melalui Komitmen Kerja Aparatur Sipil Negara - Katili, Perawati; Sakir, Moch; Musafir (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Organizational culture plays a very important role in shaping employee engagement, especially in the context of the State Civil Apparatus (ASN). Employee engagement is one of the main factors that determine the level of productivity and performance of an organization. ASN's work commitment is the connecting factor that links organizational culture with their level of engagement. This study aims to examine how organizational culture can play a role in the formation of employee engagement through ASN work commitment. The results showed that a supportive organizational culture, such as a culture based on open communication, recognition of ASN contributions, and opportunities for growth, can strengthen ASN's work commitment. With high work commitment, ASN engagement in their work increases, which leads to improved organizational performance. Therefore, it is important for government agencies to manage a positive organizational culture to increase employee engagement. Translated with DeepL.com (free version)